Entrepreneur's guide to managing growth and handling crises - Dijk, Theo J.Van (New Delhi, 2008)
Everyone knows the typical entrepreneurial success story: A couple of entrepreneurs have a great idea, work their tails off to establish the business and before long, they're set for life. Right? Hardly. Turnaround artist Theo van Dijk knows two things: First, young businesses that have survived the start-up years will face periods of stagnation. Second, every venture at some point reaches a complacent plateau, owners take their eyes off the ball and wham! A crisis charges through the door. Entrepreneurs can avoid that fate by watching for signs of trouble and taking the action steps van Dijk outlines in this book and it's worth the effort, van Dijk believes, because troubles and crises all have a silver lining, they position the company for greater, long-term growth. Entrepreneurs, predictably, become overconfident just when they think they have it made. A crisis of leadership and direction then occurs and it usually has to do with mismanaged growth.
Keywords: Entrepreneurship